An “Exercise” in Cardiac Metabolism - Kolwicz Jr., Stephen C. (Frontiers in Cardiovascular Medicine, 2018)
Research has demonstrated that the high capacity requirements of the heart are satisfied by a preference for oxidation of fatty acids. However, it is well known that a stressed heart, as in pathological hypertrophy, deviates from its inherent profile and relies heavily on glucose metabolism, primarily achieved by an acceleration in glycolysis. Moreover, it has been suggested that the chronically lipid overloaded heart augments fatty acid oxidation and triglyceride synthesis to an even greater degree and, thus, develops a lipotoxic phenotype. In comparison, classic studies in exercise physiology have provided a basis for the acute metabolic changes that occur during physical activity. During an acute bout of exercise, whole body glucose metabolism increases proportionately to intensity while fatty acid metabolism gradually increases throughout the duration of activity, particularly during moderate intensity. However, the studies in chronic exercise training are primarily limited to metabolic adaptations in skeletal muscle or to the mechanisms that govern physiological signaling pathways in the heart. Therefore, the purpose of this review is to discuss the precise changes that chronic exercise training elicits on cardiac metabolism, particularly on substrate utilization. Although conflicting data exists, a pattern of enhanced fatty oxidation and normalization of glycolysis emerges, which may be a therapeutic strategy to prevent or regress the metabolic phenotype of the hypertrophied heart. This review also expands on the metabolic adaptations that chronic exercise training elicits in amino acid and ketone body metabolism, which have become of increased interest recently. Lastly, challenges with exercise training studies, which could relate to several variables including model, training modality, and metabolic parameter assessed, are examined.